The Effects of Collectivism-Individualism on the Cooperative Learning of Motor Skill. - Luo, Yi; Sun, Yan; Strobel, Johannes (Journal of International Students, 2013)
This study examined how cultural background (collectivism vs. individualism) affects motor skill learning in a dyadic cooperative learning environment. The research context of this study was Nintendo™ Wii Tennis. Twenty college students from a Midwestern university participated in the study, among whom half were from an individualistic culture (USA) and the other half were from a collectivistic culture (China). In the study, the participants from these two backgrounds demonstrated different interaction levels and behavioral predispositions in the cooperative learning of motor skills. Both participants of individualistic background and of collectivistic background had made significant progress in the post-exercise as compared to the pre-exercise, which corroborated the benefits of cooperative learning on motor skill learning. Nevertheless, the progress made by the participants of individualistic background was statistically larger than that made by the participants of collectivistic background. Implications and limitations of this study are discussed.